2018
DOI: 10.1101/410894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3 induces multilineage maturation of human pluripotent stem cell-derived lung progenitors in 3D culture

Abstract: Although strategies for directed differentiation of human pluripotent stem cells (hPSCs) into lung and airway have been established, terminal maturation of the cells remains a vexing problem. We show here that in Collagen I 3D cultures in the absence of glycogen synthase kinase 3 (GSK3) inhibition, hPSC-derived lung progenitors (LPs) undergo multilineage maturation into proximal cells arranged in pseudostratified epithelia, type I alveolar epithelial cells and morphologically mature type II cells. Enhanced cel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…Different groups have adhered to their own methods of generating definitive endoderm, which primarily involves exposing PSCs to high concentrations of Activin A. Slight variations such as introducing WNT agonism (through WNT3a or CHIR99021) prior to [ 25 ] or alongside [ 11 , 30 , 32 , 33 ] Activin A, or additional exposure to BMP4 and FGF2 [ 23 , 25 , 29 ] during this stage exist across protocols for differentially inducing primitive streak and its anteriorization towards producing definitive endoderm. In addition, the use of embryoid bodies, which are limited by user experience and technique, has resulted in a wide range of production efficiencies for achieving this stage: from 45% CKIT + CXCR4 + EPCAM + cells [ 33 ] to >90% CKIT + CXCR4 + cells [ 23 , 25 ].…”
Section: Directed Differentiation Of Lung Epithelia Inspired By Embrymentioning
confidence: 99%
See 3 more Smart Citations
“…Different groups have adhered to their own methods of generating definitive endoderm, which primarily involves exposing PSCs to high concentrations of Activin A. Slight variations such as introducing WNT agonism (through WNT3a or CHIR99021) prior to [ 25 ] or alongside [ 11 , 30 , 32 , 33 ] Activin A, or additional exposure to BMP4 and FGF2 [ 23 , 25 , 29 ] during this stage exist across protocols for differentially inducing primitive streak and its anteriorization towards producing definitive endoderm. In addition, the use of embryoid bodies, which are limited by user experience and technique, has resulted in a wide range of production efficiencies for achieving this stage: from 45% CKIT + CXCR4 + EPCAM + cells [ 33 ] to >90% CKIT + CXCR4 + cells [ 23 , 25 ].…”
Section: Directed Differentiation Of Lung Epithelia Inspired By Embrymentioning
confidence: 99%
“…A comparison of the latter two strategies demonstrated that SHH and FGF2 are insufficient in producing reliable NKX2.1 + lung progenitors [ 25 ], possibly because FGF2 is involved in promoting thyroid lineages [ 120 ]. In general, TGFβ and BMP inhibition [ 23 ] is the basis for currently applied endoderm anteriorization strategies [ 27 , [29] , [30] , [31] , 36 , 121 ].…”
Section: Directed Differentiation Of Lung Epithelia Inspired By Embrymentioning
confidence: 99%
See 2 more Smart Citations
“…Limited access to primary human ATII cells, particularly from diseased patients, and the rapid loss of ATII marker expression and function when cultured in vitro, make it challenging to study the role of human ATII cells in IPF 19 . Recent advances have led to the successful derivation of ATII‐like cells from human pluripotent stem cells (hPSCs, including both embryonic stem cells and induced pluripotent stem cells (iPSCs)), providing a promising alternative cell source for in vitro disease modeling 20‐26 . Previous reports on hPSC‐derived lung cells showed that despite their phenotypic similarities to mature lung epithelium, these models are equivalent to human fetal lung cells, rather than representing an adult state 27,28 .…”
Section: Introductionmentioning
confidence: 99%